The Certificate of Added Competence credentialling program in family medicine: A descriptive survey of the family physician perspective of enhanced skill practices in Canada - Elma, Asiana; Vanstone, Meredith; Allice, Ilana; Barber, Cassandra; Howard, Michelle; Mountjoy, Margo; Siu, Henry; Baker, Alison; Guscott, Jesse; Tong, X Catherine; Farag, Alexandra; Grierson, Lawrence (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Introduction: The College of Family Physicians of Canada (CFPC) offers the Certificate of Added Competence (CAC) program to designate a family physician with enhanced skills. In 2015, the College expanded its program to introduce enhanced certification in four new domains: Palliative Care, Care of the Elderly, Sports and Exercise Medicine, and Family Practice Anesthesia. In this study, we elicited perceptions from Canadian family physicians with and without the CAC on practice impacts associated with the program.Methods: Active family physicians in Canada with and without CACs were surveyed between November 2019 to January 2020. Descriptive statistics were generated to describe the perceptions of family physicians regarding the CAC program and its impacts on practice.Results: Respondents agreed with several benefits of the program including enhancing the capacity to deliver comprehensive care, alleviating the burden of patient travel by increasing the availability of care in rural and remote communities, and providing opportunities to engage in various collaborative care models and new leadership roles. All respondents perceived CAC holders to pursue the certificate to meet both professional interests and community needs.Conclusions: There is a need for strong and continued investment in systemic practice improvements that incentivize the delivery of comprehensive family medicine practice.